2009
DOI: 10.1007/s10661-009-0975-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of butyltins in waters and sediments of the Mandovi and Zuari estuaries, west coast of India

Abstract: Butyltins (TBT, DBT, MBT) were measured in water and sediment samples collected from various locations in the Mandovi (10 stations) and Zuari (9 stations) estuaries during November 2007. The total butyltin (TB) in water samples varied between ~12 and 73 and from 0.5 to 77 ng Sn l -1 ; whereas, for the sediments it varied from ~ 15 to 118 and 6 to 119 ng Sn g -1 dw for the Mandovi and the Zuari estuaries, respectively. The average TB concentration in the sediments from the Zuari estuary was higher as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Many studies on methylmercury and TBT pollution have been performed in sediments, biota and fish in Asian coastal areas (Harino et al, 2009;Jiang et al, 2010;Li et al, 2009;Midorikawa et al, 2004;Nhan et al, 2005;Oh et al, 2010;Sudaryanto et al, 2002;Suehiro et al, 2006;Yawei et al, 2005), but few works dealing with water samples have been found in the literature (Bhosle et al, 2004;Cao et al, 2009;Choi et al, 2010;Garg et al, 2010;Laurier et al, 2004), and none in Vietnam. Thus, there is a need to assess the environmental impact of these pollutants in these areas through the implementation of consolidated methodologies of analysis (Monperrus et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on methylmercury and TBT pollution have been performed in sediments, biota and fish in Asian coastal areas (Harino et al, 2009;Jiang et al, 2010;Li et al, 2009;Midorikawa et al, 2004;Nhan et al, 2005;Oh et al, 2010;Sudaryanto et al, 2002;Suehiro et al, 2006;Yawei et al, 2005), but few works dealing with water samples have been found in the literature (Bhosle et al, 2004;Cao et al, 2009;Choi et al, 2010;Garg et al, 2010;Laurier et al, 2004), and none in Vietnam. Thus, there is a need to assess the environmental impact of these pollutants in these areas through the implementation of consolidated methodologies of analysis (Monperrus et al, 2005a,b).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of TBTCl have been reported in estuarine, marine, and freshwater harbors and areas that are primarily associated with boating (Pain and Cooney, 1998;Mendo et al, 2003;Jadhav et al, 2009;Ramachandran and Dubey, 2009;Garg et al, 2010;Ayanda et al, 2012). It has also been reported that the coastal waters of most Asian countries are badly affected by persistent organic pollutants (POPs) due to extensive use of these chemicals in paints and agrochemicals (Jadhav et al, 2009;Garg et al, 2010). Tributyltin was found to be the most abundant among the organotin compounds in the Mandovi and Zuari estuaries (Jadhav et al, 2009;Garg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the coastal waters of most Asian countries are badly affected by persistent organic pollutants (POPs) due to extensive use of these chemicals in paints and agrochemicals (Jadhav et al, 2009;Garg et al, 2010). Tributyltin was found to be the most abundant among the organotin compounds in the Mandovi and Zuari estuaries (Jadhav et al, 2009;Garg et al, 2010). It has been observed that even at low concentrations TBT in seawater exerts lethal effects on a wide variety of marine organisms (Bryan et al, 1988;Ayanda et al, 2012;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Jadhav et al (2009) reported the presence of organotins at toxic concentrations in the Zuari estuary, Goa, India, where butyltins contributed approximately 70-90 % of the organotins in general. The concentration of butyltins in sediments ranged from 20 to 7621 ng Sn/g Garg et al (2010). TBTCl was found to be the most abundant organotin compound in the Mandovi and Zuari estuaries of Goa, India (Jadhav et al 2009;Garg et al 2010).…”
mentioning
confidence: 99%
“…The concentration of butyltins in sediments ranged from 20 to 7621 ng Sn/g Garg et al (2010). TBTCl was found to be the most abundant organotin compound in the Mandovi and Zuari estuaries of Goa, India (Jadhav et al 2009;Garg et al 2010).…”
mentioning
confidence: 99%